Soil and Land Care: Conflicting Demands and Compounding Issues - Raman, K.V. (Journal of Soil and Water Conservation, 2022)
I feel privileged to have been invited to deliver the Dr. Y.P. Bali Memorial lecture this year. Dr. Bali was not only an outstanding soil scientist. but also a person with a great vision. He had a sworn:, commitment to the fact that increasing agricultural production and productivity on a sustainable basis can be brought about only by resource conservation and appropriate natural resource management. He realized that many of the theories and techniques adopted for the soils of the temperate and semi-temperate zones may not be strictly applicable for the arid and semiarid zones of tropical soils and tried to evolve parameters that are more suitable for these regions. Interestingly, he did all these at a time when the present day concepts of sustainability had not been fully developed, and with facilities and circumstances that would have been dubbed as primitive by today’s standards. While acknowledging his contributions to Indian science, I join all of you in paying our humble tribute to Dr. Bali for his contributions to Soil Science in general, and resource conservation in particular. I also commend his family for their thoughtful gesture in commemorating his memory through these lectures.